Correlates of cigarette smoking among adolescents in India - Jai Kishun; Anup Kumar; Uttam Singh (Wolters Kluwer Medknow Publications, 2021)
Background: The use of cigarettes/tobacco among adolescents is quite high in India. Worldwide, nearly, all (88%) initiation of smoking occurs before the age of 18 years. Smoking caused about 1 million deaths or 10% of all deaths in India, with about 70% of these deaths occurring at the ages of 30-69 years. Aims and Objectives: Different correlates of cigarette smoking among adolescents were investigated, which may help to improve public health interventions in India. Materials and Methods: Global Youth Tobacco Survey data collected in India during 2009 were taken. Bivariate analysis, logistic regression, receiver operating characteristic, and nomogram were used to examine association between exposure and outcome variables. Cigarette smoking within the past 30 days preceding the survey was the outcome variable while independent variables were age, education, gender, parental smoking, people smoking at home/smoking in the presence of adolescents, felt boys/girls who smoke have more friends, accepting cigarette offered by one of the best friends, perception of attractiveness of boys/girls who smoke, perception smoking makes one loss or gain weight, and perception cigarettes smoking harmful. Results: 11768 adolescents participated, of which 9951 (48% males and 52% female) responded on cigarette smoking. Current cigarette smoking was associated with female gender (odds ratio [OR]: 0.68; 95% confidence interval [CI]: 0.52-0.90), parental smoking (OR: 1.00; 95% CI: 0.62-1.60), smoking cigarette at home (OR: 3.66; 95% CI: 2.64-5.09), and smoking cigarette in presence of adolescent (OR: 4.14; 95% CI: 2.92-5.87). Observed associations between the outcome and exposure variables reported in this study should be considered in the design of public health interventions. Conclusion: To eliminate smoking habits, efforts should also be made in the exploration of new ideas and their implementation by the public health experts in collaboration with international agencies, various nongovernmental organizations, and academic and research institutions. Let's plan for active action to make smoke-free environment based on evidence.